Dekontaminasi Parameter Biologi dan Pathogen Menggunakan Biofilm Konsorsium Bergerak Dilanjutkan dengan Intergrasi Pengolahan Fisik (Pengendapan-Sterilisasi) Secara Simultan - Rizka Novembrianto; Restu Hikmah Ayu Murti; Muslikha Nourma Rhomadhoni (Al-Ard: Jurnal Teknik Lingkungan, 2023)
The amount of domestic wastewater without prior treatment is discharged into water bodies so that it is felt that the quality is decreasing day by day. Organic content and microorganisms are a concern in terms of quality. The high content of organic and microorganisms such as Total coliform. Decreasing these parameters is the main goal in this study. In the aerobic process, organic processing uses an air supply of 20 L/min in suspended and attached treatment for attached media using K5 caldnes media and spiked bioball, each of which is 30% of the reactor volume, preceded by the seeding and acclimatization process. Variations in processing time used were suspended for 2 hours and attached for 6 hours and vice versa. Furthermore, it is processed by simultaneous physical processing, namely the process of deposition and sterilization with exposure and deposition times of 2 to 6 hours. Based on the results of the study showed that seeding and acclimatization were carried out for 21 days. The best processing was obtained using suspension for 2 hours, attached for 6 hours on kaldnes K5 media and precipitation as well as exposure to ultraviolet light for 6 hours showed a decrease in COD of 92.85% and for Total coliforms of 98.67%. Keywords: domestic, organic, media, ultraviolet